1998
DOI: 10.1128/mcb.18.10.5670
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Myogenic Transcription Factor MyoD by the Ubiquitin Pathway In Vivo and In Vitro: Regulation by Specific DNA Binding

Abstract: MyoD is a tissue-specific transcriptional activator that acts as a master switch for skeletal muscle differentiation. Its activity is induced during the transition from proliferating, nondifferentiated myoblasts to resting, well-differentiated myotubes. Like many other transcriptional regulators, it is a short-lived protein; however, the targeting proteolytic pathway and the underlying regulatory mechanisms involved in the process have remained obscure. It has recently been shown that many short-lived regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
115
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 45 publications
4
115
0
Order By: Relevance
“…Because MyoD engages in a network of transcriptional activities in C2C12 cells as well as in other cells of the muscle lineage, one potential explanation for the inaccessibility of the hypophosphorylated MyoD species to phosphorylation and subsequent ubiquitin-proteasome-mediated degradation is that it is actively engaged in the transcription process and is possibly associated with DNA or other binding partners. Consistent with this notion, it has been shown that the formation of MyoD-ubiquitin conjugates is inhibited by the specific DNA sequence to which MyoD binds; conjugation and degradation of a MyoD mutant protein that lacks the DNA-binding domain are not inhibited (19). Moreover, substitution of serine 200 in MyoD to a nonphosphorylatable alanine abolished the slower migrating hyperphosphorylated form of MyoD; this mutant also significantly enhances both the muscle gene-specific transcriptional activity of MyoD and the ability of MyoD to induce myogenic conversion of nonmuscle cells (32).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Because MyoD engages in a network of transcriptional activities in C2C12 cells as well as in other cells of the muscle lineage, one potential explanation for the inaccessibility of the hypophosphorylated MyoD species to phosphorylation and subsequent ubiquitin-proteasome-mediated degradation is that it is actively engaged in the transcription process and is possibly associated with DNA or other binding partners. Consistent with this notion, it has been shown that the formation of MyoD-ubiquitin conjugates is inhibited by the specific DNA sequence to which MyoD binds; conjugation and degradation of a MyoD mutant protein that lacks the DNA-binding domain are not inhibited (19). Moreover, substitution of serine 200 in MyoD to a nonphosphorylatable alanine abolished the slower migrating hyperphosphorylated form of MyoD; this mutant also significantly enhances both the muscle gene-specific transcriptional activity of MyoD and the ability of MyoD to induce myogenic conversion of nonmuscle cells (32).…”
Section: Discussionsupporting
confidence: 56%
“…Studies in a cell culture model that has a phenotype similar to that observed in myoblast cultures derived from myotonic dystrophy 1 patient muscle suggest that C2C12 myogenic differentiation is disrupted by mutant myotonic dystrophy protein kinase 3Ј-untranslated region transcripts via posttranscriptional reduction of MyoD protein levels (27). Previous studies in vitro or in non-muscle cells also show that MyoD degradation is regulated by phosphorylation, DNA binding, and protein-protein interactions (19,28). Phosphorylation of MyoD is required for its rapid degradation.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Additionally, some studies show that certain transcription factors with mutations in the DNA binding domain become resistant to degradation (18). On the other hand, some transcription factors are resistant to degradation when bound, such as p53 (19) and MyoD (20). Because situations exhibiting both binding vulnerability and binding protection exist, we will investigate both scenarios here in the context of an autoregulated gene surrounded by a variable number of nonfunctional transcription factor binding sites.…”
mentioning
confidence: 99%